Excessive Politicization of Universities: Threats toward Academic Freedom - Sejan, Sakhawat Sajjat (Kathmandu School of Law Review, 2024)
University is designated as the marketplace of ideas. The marketplace transpires transcendent values among the students to build upcoming generations and generate new knowledge. For that academic freedom of the teachers and students is inevitable. Usually, teachers in universities must enjoy three rights to ensure academic freedom. S/he must have freedom of research and publication, freedom of teaching and freedom of speaking on different issues as citizens. Freedom of teaching is perceived as core academic speech and freedom of speaking on different issues is confined within extra mural (political) and intra-mural (public issues) speeches. This means a person belonging to academia has the scope of opining on different issues of a country whether it be academic or non-academic. As far as s/he speaks from his/her subjective expertise with objectivity, his/her speech is a fundamental human right. The absence of free speech in academia will not bring new and radical ideas through questioning the current system. But the scenario is upside down in Bangladesh. Here, the faculty members or students don’t enjoy academic freedom or secure academic environment due to the excessive politicization of universities. Though politicization could have accelerated academic freedom by entertaining dissenting opinions, but in Bangladesh it creates a chilling effect on the core academic, intra-mural and extra-mural speech of the faculty members. This will endanger the academia of Bangladesh by squeezing its role of social/state reformation and nation-building. Hence, this article focuses on the violation of academic freedom in Bangladesh through excessive politicization of Universities and endeavors to find political influence-free academia through the lens of freedom of speech.